Washback in Language Testing: a Review of the Concept and its Implications to Innovation in Education - حواجلي, أحمد شوقي (Revues faculté des lettres et des langues, 2014)
مصطلح «Washback » أو ظاهرة تأثير الامتحان على العملية التدريسية والتعليمية هي فعل موجود في الممارسات اليومية لمدرسي اللغات الأجنبية. هذا التأثير قد يكون له وجهان مختلفان. من جهة وجه إيجابي، ومن جهة أخرى وجه سلبي . الإشكالية المطروحة هي أنه على الرغم من وجود هذه الظاهرة إلا أن علمها مقصور على قلة منهم وكثيرهم يجهلونها. في إطار هذه الفكرة، يأتي هذا المقال لإماطة اللثام وتسليط الضوء على هذه الظاهرة من خلال توضيح طبيعتها، وظائفها، وآليات حدوثها. بالإضافة إلى هذا، يحاول هذا المقال توضيح العلاقة بين ظاهرة تأثير الامتحان أو ما يسمى «Washback »، ومجال الإبداع التربوي.   Washback is a concept used to refer to a phenomenon associated with the influence language tests exert on teaching and learning. Washback can be positive, as well as it can be negative. The present article is a serious attempt in the field of testing research that seeks to shed light on the concept washback. The purpose of the article is to help practitioners to get a clear and large picture on the nature, functions and mechanisms of the term under study. Besides, this presentation aims to display how this phenomenon can be a lever to provide models of innovation in education